Mental Ill Health, Recovery and the Family Assemblage - Price-Robertson, R.; Manderson, L.; Duff, Cameron (2017)
The recovery approach is now among the most influential paradigms shaping mental health policy and practice across the English-speaking world. While recovery is normally presented as a deeply personal process, critics have challenged the individualism underpinning this view. A growing literature on “family recovery” explores the ways in which people, especially parents with mental ill health, can find it impossible to separate their own recovery experiences from the processes of family life. While sympathetic to this literature, we argue that it remains limited by its anthropocentricity, and therefore struggles to account for the varied human and nonhuman entities and forces involved in the creation and maintenance of family life. The current analysis is based on an ethnographic study conducted in Australia, which focused on families in which the father experiences mental ill health. We employ the emerging concept of the “family assemblage” to explore how the material, social, discursive and affective components of family life enabled and impeded these fathers’ recovery trajectories. Viewing families as heterogeneous assemblages allows for novel insights into some of the most basic aspects of recovery, challenging existing conceptions of the roles and significance of emotion, identity and agency in the family recovery process.